Le Néolithique du nord-est de la France et des régions limitrophes (Éditions de la Maison des sciences de l’homme, 2022)
Organised for the first time in Lorraine, this 13th interregional meeting on the Neolithic quite naturally privileged the origins of this period in eastern France: important synthesis concerning the region as well as contributions related to adjoining Germany and Belgium are to be found. Amongst others the question, still controversial, concerning the Rubané and Cardial influences on the French Neolithic is largely discussed here. Finally several articles concerning later stages of the Neolithic, notably the Michelsberg, are presented here.